Custom Menu Msme Goods Management Application System Based On Android - Gemawaty, Cut Asiana; Sulaiman, Han; Sutrisno, Danang (Journal of Renewable Engineering, 2024)
The Android-based inventory management application for MSMEs is designed to enhance efficiency and accuracy in inventory management for micro, small, and medium enterprises (MSMEs). The application offers features such as adding, reducing, and updating stock items, tracking transaction history, and generating real-time stock and sales reports. With an intuitive and user-friendly interface, this application simplifies inventory management for users. User data security is ensured through secure authentication, data encryption, and regular backups. Continuous maintenance and user support are also provided to ensure the application remains stable and meets user needs. This application contributes to the digitalization process of MSMEs, helping them improve operational efficiency and compete in an increasingly digital market.